Biosimilars in supportive care. Issue 4 (July 2020) - Foreman, Emma
Abstract : Purpose of review: This review covers recent publications relating to the use of biosimilar medicines in the supportive care of cancer patients, and broader publications focussed on the benefits and challenges of implementing biosimilars into clinical practice. Recent findings: A metaanalysis and a number of systematic literature reviews have confirmed that the safety and efficacy of biosimilar versions of epoetin-α, filgrastim and infliximab are equivalent to those of their corresponding reference biologics. New guidelines have been issued concerning the interchangeability of biosimilars and the practice of substituting a biosimilar in place of a prescribed reference product. The introduction of biosimilars into a health system has been shown to improve patient access to treatment while also delivering cost savings, however, there are a number of barriers that can prevent or delay the adoption of biosimilars into clinical practice which must be overcome for the potential benefits of biosimilars to be realized. Summary: There is a large amount of data to demonstrate that supportive care biosimilars are well tolerated and effective, with over 10 years of experience in Europe. We can learn from the challenges faced when introducing biosimilars into supportive care to facilitate the introduction of newer biosimilars into the treatment setting.